Estimating peak oxygen uptake based on postexercise measurements in swimming - Chaverri, D.; Iglesias, X.; Schuller, T.; Hoffmann, U.; Rodriguez, F. (Applied Physiology, Nutrition, and Metabolism, 2016)
To assess the validity of postexercise measurements in estimating peak oxygen uptake (VO2peak) in swimming, we compared oxygen uptake (VO2) measurements during supramaximal exercise with various commonly adopted methods, including a recently developed heart rate — VO2 modelling procedure. Thirty-one elite swimmers performed a 200-m maximal swim where VO2 was measured breath-by-breath using a portable gas analyzer connected to a respiratory snorkel, 1 min before, during, and 3 min postexercise. VO2peak(-20-0) was the average of the last 20 s of effort. The following postexercise measures were compared: (i) first 20-s average (VO2peak(0-20)); (ii) linear backward extrapolation (BE) of the first 20 s (BE(20)), 30 s, and 3 × 20-, 4 × 20-, and 3 or 4 × 20-s averages; (iii) semilogarithmic BE at 20 s (LOG(20)) and at the other same time intervals as in linear BE; and (iv) predicted V?O2peak using mathematical modelling (pVO2(0-20)]. Repeated-measures ANOVA and post-hoc Bonferroni tests compared V?O2peak (criterion) and each estimated value. Pearson`s coefficient of determination (r2) was used to assess correlation. Exercise VO2peak(-20-0) (mean ± SD 3531 ± 738 mL/min) was not different (p > 0.30) from pVO2(0-20) (3571 ± 735 mL/min), BE(20) (3617 ± 708 mL/min), or LOG(20) (3627 ± 746 mL/min). pVO2(0-20) was very strongly correlated with exercise VO2peak (r2 = 0.962; p < 0.001), and showed a low standard error of the estimate (146 mL/min, 4.1%) and the lowest mean difference (40 mL/min; 1.1%). We confirm that the new modelling procedure based on postexercise VO2 and heart rate measurements is a valid and accurate procedure for estimating V?O2peak in swimmers and avoids the estimation bias produced by other methods.